Challenging norms, protecting forests: The agency and negotiation strategies of women rangers in Aceh, Indonesia - Darwin, Rizkika Lhena; Masni, Melly; Rahman, Bobby; Fitri, Cut Dian; Suwardi, Anna Christi; Septiana, Nabila Amira (UIN Ar-Raniry Banda Aceh, 2025)
This research analyzes the strategic agency of Mpu Uteun, a women-led conservation group in Aceh, Indonesia, that emerged in response to severe environmental degradation within a patriarchal social context. Grounded in the theoretical framework of women's agency and empowerment, this research examines the negotiation mechanisms that these female forest guardians employ across multiple spheres—domestic, communal, economic, and state—to legitimize their roles in environmental governance as they navigate socio-cultural barriers. Conducted within a qualitative design, this research employed secondary data examined through thematic narrative analysis. The findings revealed that the agency of Mpu Uteun is rooted in a collective experience of ecological disaster, which motivates proactive conservation measures such as forest patrols, reforestation, and disaster mitigation. The group's success hinges on sophisticated negotiation strategies: they renegotiated domestic roles to accommodate public activism, navigate communal resistance through inclusive tactics and non-confrontational approaches toward illegal loggers, and, crucially, secure formal legitimacy from the state by obtaining a customary forest management permit. This research concludes that Mpu Uteun exemplifies an effective model of community-based conservation while fundamentally transforming the gendered landscape of natural resource governance. Thus, this research advances understanding of women’s environmental agency, demonstrating how strategic negotiation dismantles patriarchal barriers and informs inclusive conservation policy.